Reseña bibliográfica: La enseñanza del Derecho Internacional Público. La influencia de la cátedra de Luis A. Podestá Costa en la Universidad de Buenos Aires - Drnas de Clément, Zlata (2023)
This work corresponds to the doctoral thesis of Leopoldo M. A. Godio, directed by Professor Emeritus of the University of Buenos Aires Doctor Tulio Ortiz, who prefaces this publication. The thesis "defended on November 20, 2022" has received the highest grade: 10 (excellent), with recommendation for the Faculty Award and publication